Bentuk-bentuk Badan Hukum Unit Usaha Badan Usaha Milik Desa - Purwaningsih, Sri Budi; Mediawati, Noor Fatimah; Mursyidah, Lailul; Faizin, Moh.; Fatthurahman, M. Aditya; Siswapranata , Fadiana Zahra (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
The recent development of Village-Owned Enterprises (BUMDesa) along with their business units must entail separation, which means that the business units of BUMDesa have their own legal entity as separate subjects of law from the main legal entity of BUMDesa. The purpose of the study is to determine the appropriate legal form for the business units of BUMDesa. The research method used in this study is the statutory approach, linking the regulations concerning BUMDesa with relevant legal theories. The findings of the study conclude that the legal standing of BUMDesa as a legal entity is established based on Village Regulations, both from the perspective of public and private law. The differentiation of BUMDesa's legal status from the perspective of public law is largely determined by the law, while from the perspective of private law, registration is required to fulfill the principle of publicity. The legal form of the business units of BUMDesa can be established as either a Cooperative or a Limited Liability Company (PT). The choice between a Cooperative or Limited Liability Company is based on the governance characteristics of the BUMDesa business units. The consequence of this independent legal status for the business units of BUMDesa allows them to effectively carry out their business activities to achieve profits as commercial enterprises, prioritizing the primary goal of optimizing the welfare of the village community.